2017
DOI: 10.1002/art.40049
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Subcutaneous Belimumab in Systemic Lupus Erythematosus: A Fifty‐Two–Week Randomized, Double‐Blind, Placebo‐Controlled Study

Abstract: ObjectiveTo assess the efficacy and safety of subcutaneous (SC) belimumab in patients with systemic lupus erythematosus (SLE).MethodsPatients with moderate‐to‐severe SLE (score of ≥8 on the Safety of Estrogens in Lupus Erythematosus National Assessment [SELENA] version of the SLE Disease Activity Index [SLEDAI]) were randomized 2:1 to receive weekly SC belimumab 200 mg or placebo by prefilled syringe in addition to standard SLE therapy for 52 weeks. The primary end point was the SLE Responder Index (SRI4) at w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
305
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 311 publications
(346 citation statements)
references
References 42 publications
(62 reference statements)
17
305
1
3
Order By: Relevance
“…The SRI-6 response rate in the control subjects in this study (42.3%) was very high compared with prior SLE trials conducted in subjects with baseline SELENA-SLEDAI scores of ≥6 (20.4%,1 29.2%,3 27.0%4) or ≥8 (33.7%16). Analysis of SRI-6 was based on a logistic regression model with the following covariates fitted as explanatory variables: region, SELENA-SLEDAI at baseline (<=12, >12), UPCR at screening (<226, ≥226 mg/mmol), prednisone dose at baseline (<median dose, ≥median dose) and immunosuppressant use at baseline (yes, no).…”
Section: Discussionmentioning
confidence: 51%
“…The SRI-6 response rate in the control subjects in this study (42.3%) was very high compared with prior SLE trials conducted in subjects with baseline SELENA-SLEDAI scores of ≥6 (20.4%,1 29.2%,3 27.0%4) or ≥8 (33.7%16). Analysis of SRI-6 was based on a logistic regression model with the following covariates fitted as explanatory variables: region, SELENA-SLEDAI at baseline (<=12, >12), UPCR at screening (<226, ≥226 mg/mmol), prednisone dose at baseline (<median dose, ≥median dose) and immunosuppressant use at baseline (yes, no).…”
Section: Discussionmentioning
confidence: 51%
“…Since its approval by the FDA, "real-world" clinical experience with belimumab has largely been positive [61][62][63]. Also since approval of belimumab as an IV drug, a randomized, double-blind, placebo-controlled trial of belimumab (200 mg fixed dose SC weekly through week 52) plus SOC in SLE demonstrated a statistically significantly greater response rate among belimumab-treated subjects than among placebo-treated subjects [64]. It is anticipated that the FDA will soon approve the SC formulation, thereby giving SLE patients the option of receiving their medication away from an infusion center or a medical clinic.…”
Section: ) Belimumabmentioning
confidence: 99%
“…Of the eight late-stage clinical trials of BAFF antagonists in SLE reported to date in complete manuscript form, only four met their respective primary endpoints: each of the three phase-III trials of belimumab [57,58,64], and one of the two phase-III trials of tabalumab [69]. The phase-II belimumab trial, the phase-IIb blisibimod trial, the phase-II/III atacicept trial, and one of the two phase-III tabalumab trials all failed [67,70,72,73].…”
Section: Can the Limited Clinical Efficacy Of Baff Antagonists Be Ovementioning
confidence: 99%
See 1 more Smart Citation
“…OLE AEs were those occurring on or after the first OL dose. Efficacy evaluations were conducted, at reduced frequency, as per the DB phase1 . Results: Overall, 677 patients completed the DB phase, 662 entered the OLE; 625 completed.…”
mentioning
confidence: 99%